Analysis and Critique of the Opportunities, Challenges and Mutual Benefits of Social-Private Sector Partnerships - Soliman, Marwa (2010)
With increased pressures on all three sectors in the economy and the blurring of roles and responsibilities, cross-sector collaboration is a growing trend. This management project researches the topic of social-private sector partnerships. Through analysis of various forms to partnerships between organizations and their motivations as well as capturing the learning from partnership experiences, the research aims to provide recommendations on practical approaches to the successful management of such partnerships. Other than providing a comprehensive literature review, the management project analyses its findings based on the investigation of the experiences of four partnerships between social and private sector organizations, the results of which are reflected and critiqued through the main stages of partnership management: formation, implementation and outcomes.